Inventing Images: Constructing and Contesting Gender in Thinking about Electroacoustic Music - McCartney, Andra (Leonardo Music Journal, 1995)
The author explores symbolic imagery in the world of electroacoustic music, as presented in both popular music publications and the language of 14 Canadian women composers. While mainstream discourse uses imagery that emphasizes power and control, these composers use metaphors of painting, dancing, sustenance, addiction, wilderness, meetings, circuitry, curses, locks, boxes, blessings and desire to describe their work. This imagery suggests different ways for artists to think about their interaction with technology.

In and out of the studio - McCartney, Andra (Université Concordia, 2013)
In and out of the studio was a collaborative multimedia project which aimed to examine and document the working methods of several female sound producers, from a variety of media (such as radio, film sound, television, hypermedia, performance art) and in different institutional contexts. The website, which is compiled in this document, was one element in an effort to establish a greater sense of community among women sound producers who are separated by geographic space, occupation or disciplinary boundaries.

In and Out of the Sound Studio: Introduction - McCartney, Andra; Waterman, Ellen (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
Dans l’introduction à ce numéro spécial d’Intersections, Andra McCartney et Ellen Waterman présentent les Dedans et Dehors du Studio, un projet de recherche ethnographique inter-universitaire soutenu financièrement par le CRSH du Canada de 2001 à 2005. L’équipe de recherche a étudié les idées et pratiques des artisans sonores canadiens, se penchant particulièrement sur le sujet de la relative invisibilité et inaudibilité des femmes, réfléchissant aux différentes manières dont les technologies et pratiques sonores peuvent être orientées sexuellement. Dans leurs essais, les auteures discutent des relations trouvées entre les termes genre, son et technologie, du point de vue aussi bien terminologique, qu’esthétique, du mentorat, ou encore méthodologique et théorique. Les contributions de McCartney, Diamond, Laplante, Labrosse, Marsh et Bosma sont ici discutées.